Dos casas alejadas de centros urbanos (1997)
Casa Pollitzer, Gral.Pacheco, Pcia. de Bs. As., arq.Juan I.Ramos; Casa Grondona, La Barra de Maldonado, Uruguay, arq. San Martín-Lonné
Keywords: VIVIENDAS DE VACACIONES; VIVIENDAS SUBURBANAS